The effect of grit on leisure time physical activity. An Application of Theory of Planned Behaviour - VELLO HEIN; ANDRE KOKA; HANNA KALAJAS-TILGA; HENRI TILGA; LENNART RAUDSEPP (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2020)
Background: Grit as personal trait has an important role in achieving different behavioural outcomes. The present study aimed to test the validity of an extended model of the Theory of Planned Behaviour, in which domains of grit, such as perseverance of effort and consistence of interest are mediators between the attitude and intention, and between attitude and self-reported leisure time physical activity behaviour. Material and methods: The participants were school children: 106 boys (M age = 13.00, SD = 0.98) and 240 girls (M age = 13.13, SD = 0.95) Structural equation modelling (SEM) was used to test the effects of perseverance of effort, consistency of interest, attitude, and intention on leisure time physical activity. Results: The model demonstrated acceptable fit with the data. Direct relationships between perceived attitude and dimensions of grit were statistically significant. Attitude related directly and indirectly via intention to self-reported physical activity. A significant indirect effect from attitude to leisure time physical activity via perseverance of effort followed. Conclusions: Beyond the attitude, perseverance of effort is an important predictor of leisure time physical activity among schoolchildren.